Space : The Ultimate Guide - Gallagher;Belinda (Australia Five Mile Press, 2007)
Discover amazing facts about the Universe and its galaxies, stars and planets, providing an insight into astronomical discoveries and technology. Includes two giant posters of the Universe and the constellations of the night sky and glow-in-the-dark stars to create your own constellations. Ages 8+.